Unsilencing the past : track two diplomacy and Turkish-Armenian reconciliation - Phillips, David L. (David Lawrence), 1959- (Berghahn Books, 2005)
The Turkish-Armenian conflict has lasted for nearly a century and still continues in attenuated forms to poison the relationship between these two peoples. The author, Senior Fellow and Deputy Director of the Center for Preventive Action at the Council on Foreign Relations and previously advisor to the United Nations, undertook, as head of the Turkish-Armenian Reconciliation Committee, to bring the two sides together and to work with them towards a peaceful resolution of the enmity that had made any contact between them taboo.His lively account of the difficult negotiations makes fascinating reading; it shows that the newly developed "track-two diplomacy" is an effective tool for reconciling even intractable foes through fostering dialog, contact and cooperation.